Helping doctoral students write pedagogies for supervision - Kamler, Barbara; Thomson, Pat (Routledge, 2014)
"Helping Doctoral Students Write offers a proven approach to effective doctoral writing. By treating research as writing and writing as research, the authors offer pedagogical strategies for doctoral supervisors that will assist the production of well-argued and lively dissertations. It is clear that many doctoral candidates find research writing complicated and difficult, but the advice they receive often glosses over the complexities of writing and/or locates the problem in the writer. Kamler and Thomson provide a highly effective framework for scholarly work that is located in personal, institutional and cultural contexts. The pedagogical approach developed in the book is based on the notion of writing as a social practice. This approach allows supervisors to think of doctoral writers as novices who need to learn new ways with words as they enter the discursive practices of scholarly communities. This involves learning sophisticated writing practices with specific sets of conventions and textual characteristics. The authors offer supervisors practical advice on helping with commonly encountered writing tasks such as the proposal, the journal abstract, the literature review and constructing the dissertation argument. The first edition of this book has helped many academics and thousands of research students produce better written material. Now fully updated the second edition includes: Examples from a broader range of academic disciplines A new chapter on writing from the thesis More advice on reading and note taking, performance and conferences, Further information on developing a personal academic writing style, and Advice on the use of social media (blogs, tweets and wikis) to create trans-disciplinary and trans-national networks and conversations"-- Provided by publisher.